2016
DOI: 10.20937/rica.2016.32.04.06
|View full text |Cite
|
Sign up to set email alerts
|

Vermicompost as an Alternative of Management for Water Hyacinth

Abstract: Aquatic weeds, such as Eichhornia crassipes (Mart.) Solms (water hyacinth) can be used as raw material for vermicompost. Vermicompost is the product of microbial decomposition of organic waste through the digestive tracts of earthworms. The aim of this work was to use water hyacinth to obtain stable and mature vermicompost. Three treatments were performed for vermicomposting, treatment one with 100 % of water hyacinth, treatment two with 100 % of cow manure and treatment three with 50 % of water hyacinth and 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 24 publications
3
6
0
Order By: Relevance
“…For instance, in the study conducted by Olivera Viciedo, et al [61] on the response of radish to difference ammonical nitrogen concentrations in absence and presence of silicon, observed highest sensitivity in treatments without silicon. In the cow manure treatment with E. fetida only, the highest germination observed agree with findings of Bernal, et al [62] who found increased GI value of radish from between 24 to 120 h of germination using cow manure vermicompost using E. fetida. Therefore, the results showed low levels of phytotoxic substances.…”
Section: 5supporting
confidence: 90%
“…For instance, in the study conducted by Olivera Viciedo, et al [61] on the response of radish to difference ammonical nitrogen concentrations in absence and presence of silicon, observed highest sensitivity in treatments without silicon. In the cow manure treatment with E. fetida only, the highest germination observed agree with findings of Bernal, et al [62] who found increased GI value of radish from between 24 to 120 h of germination using cow manure vermicompost using E. fetida. Therefore, the results showed low levels of phytotoxic substances.…”
Section: 5supporting
confidence: 90%
“…The results indicate that the processing time in ASP is about 15-20 days shorter than of the processing and maturation time of compost in the vermicomposting method. A stable and mature vermicompost was obtained after 110 days which is in agreement with the results of a similar research conducted by Alvarez-Bernal et al (2016). Gupta et al (2007) reported 147 days to obtain stable and mature vermicompost.…”
Section: Resultssupporting
confidence: 91%
“…The organic matter content and cation exchange capacity of final vermicompost were high, indicating that it was rich in nutrients and therefore suitable as organic amendment. These results are in agreement with the results of a research conducted by Alvarez-Bernal et al (2016). CEC was measured about 100 and 96 meq/100 g for vermicompost and ASP-finished product, respectively.…”
Section: Comparison Of Chemical Characteristics Of Finished Compost Isupporting
confidence: 92%
“…The resulting compost functions as a eutrophic natural manure and soil stimulant [ 48 ]. Vermicompost is obtained when organic waste decomposed by microbes in the digestive tracts of earthworms [ 49 ]. Water hyacinth has been found to be a very good vermicomposting raw material.…”
Section: Introductionmentioning
confidence: 99%
“…Water hyacinth has been found to be a very good vermicomposting raw material. In combination with cow dung, water hyacinth was successfully converted into vermicompost in Zimbabwe [ 50 ] but, in fact, was found to yield better vermicompost when used alone as a substrate for earthworms [ 49 ]. Vermicomposting E. crassipes from Lake Victoria in Kenya yielded richer vermicompost [ 51 ].…”
Section: Introductionmentioning
confidence: 99%